Autonomic dysfunction in people with neuromyelitis optica spectrum disorders. (May 2020) - Crnošija, Luka; Krbot Skorić, Magdalena; Andabaka, Marko; Junaković, Anamari; Martinović, Vanja; Ivanović, Jovana; Mesaroš, Šarlota; Pekmezović, Tatjana; Drulović, Jelena; Habek, Mario
Aims: To determine the difference in autonomic symptom burden measured with the Composite Autonomic System Score-31 (COMPASS-31) and presence of objective dysautonomia in people with neuromyelitis optica spectrum disorders (pwNMOSD) compared to people with multiple sclerosis (pwMS). Design/Methods: Twenty pwNMOSD and 20 pwMS, matched for age, sex, and disease duration, were enrolled. All patients completed the COMPASS-31. The quantification of cardiovascular autonomic dysfunction (CAD) was made using the two indices of the Composite Autonomic Scoring Scale (CASS): adrenergic index (AI) and cardiovagal index (CI). Results: In all pwNMOSD, COMPASS-31 was >0. Sympathetic dysfunction was present in 8 (40%), parasympathetic dysfunction in 10 (50%), and orthostatic hypotension in 6 (30%) pwNMOSD. This group of patients had higher frequency and level on the pupillomotor domain of the COMPASS-31 compared to pwMS ( p  = 0.048 and p  = 0.006, respectively). A binary logistic regression model showed that drop in diastolic blood pressure (dBP) during tilt-table test and normal function of autonomic nervous system, defined as AI = 0 and CI = 0, were independent predictors of pwNMOSD ( p  = 0.042 and p  = 0.029, respectively). If CAD was present, it was significantly worse in pwNMOSD compared to pwMS ( p  = 0.003). Conclusion: Significant proportion of pwNMOSD experience dysautonomia, which seems to be different from dysautonomia observed in pwMS.